Influence of a surface conditioner to pre-sintered zirconia on the biaxial flexural strength and phase transformation. Issue 3 (March 2018) - Sawada, Tomofumi; Schille, Christine; Zöldföldi, Judit; Schweizer, Ernst; Geis-Gerstorfer, Jürgen; Spintzyk, Sebastian
Highlights: A novel zirconia surface modification approach was proposed in this study. A conditioner was applied on pre-sintered Y-TZP surface before sintering. The phase transformation and flexural strength of Y-TZP specimens were evaluated. X-ray diffraction revealed the phase stability in conditioner-coated Y-TZP. This graded glass/zirconia structure did not affect the biaxial flexural strength. Abstract: Objectives: To assess the influence of a surface conditioner applied to pre-sintered yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) on the biaxial flexural strength and phase transformation. Methods: Conditioner-coated specimens (12 mm diameter × 0.8 mm thickness) were prepared by application of a slurry conditioner using a brush on pre-sintered Y-TZP discs, followed by sandblasting with 50-μm Al2 O3 after sintering (C-SB) or no further treatment (C-NT). The remaining conditioner-free specimens were subjected to sandblasting before sintering (NC-SB) or were maintained without treatment (NC-NT). Surface roughness measurements and scanning electron microscopy (SEM) in conjunction with energy dispersive X-ray spectroscopy (SEM-EDX) were performed for surface characterizations. The phase transformation of Y-TZP was identified by X-ray diffraction (XRD), and the biaxial flexural strength was measured using the piston-on-three-ball test according to ISO 6872:2015. The data were analyzed using nonparametric Kruskal–Wallis tests and Weibull distributions with the maximum likelihood estimation. Results: Sandblasting resulted in significantly rougher surfaces, irrespective of conditioner application. Conditioner layers were observed on surfaces in the C-NT and C-SB specimens. Monoclinic contents were present in a very small amount in the C-SB specimens. Both median biaxial flexural and characteristic strengths of all specimens exceeded ISO 6872:2015 requirements (Class 5: >800 MPa), except the NC-SB specimens which showed significantly the lowest strength ( p  < 0.001). Although no statistical difference was observed in Weibull modulus among the specimens ( p  = 0.598), the NC-SB specimens showed the highest. Significance: Surface conditioner application does not affect the biaxial flexural strength and phase stability of Y-TZP and can be considered practical for clinical use.